An evaluation of customer retention strategies used in the hotel industry with a specific focus on Flamboyant hotel (2010-2016) - Rufasha, Shoorai (Midlands State University, 2018)
This research sought to evaluate the customer retention strategies used in the hotel industry from (2010-2016). The study was motivated by the persistent loss of customers at Flamboyant Hotel despite its implementation of customer retention strategies. The research aimed at determining the importance of customer retention management practises of Flamboyant Hotel. The study also focused on deriving the factors which influence the choice of customer retention strategies. Furthermore the research tried to determine the challenges faced in implanting customer retention strategies. The research focused on the major theories of customer retention which are the relationship commitment model, holistic approach and the conversion model. The concept of customer attrition was also discussed in the study. Descriptive research method was used in order to gain a better understanding of the problem at hand which is customer loss at the hotel. Questionnaires and Interviews were used as data collection instruments. A sample size of 150 customers, 5 managers and 20 employees was used. The researcher used tables in data presentation and inductive technique was used as a data analysis tool. The findings indicated that if a company effectively implements customer retention strategies, its customer loyalty will be enhanced. However failure to effectively implement customer retention strategies leads to customer loss. The study findings also illustrated that the company was failing to effectively implement retention strategies because of the cost that is brought about by implementing retention strategies. Furthermore customers were dissatisfied the hotel’s service, ambiance and service recovery systems.